Regulation of production of the blue pigment indigoidine by the pseudo γ-butyrolactone receptor FarR2 in Streptomyces lavendulae FRI-5 - Yohanes Novi Kurniawan (2018)
© 2015 The Society for Biotechnology, Japan. The γ-butyrolactone autoregulator signaling cascade is widely distributed among Streptomyces species as an important regulatory system of secondary metabolism. In Streptomyces lavendulae FRI-5, a γ-butyrolactone autoregulator IM-2 and the IM-2 specific receptor FarA control production of the blue pigment indigoidine together with two types of antibiotics: d-cycloserine and the nucleoside antibiotics. Here, we demonstrated by in silico analysis that farR2 (a farA homologue), which is located in a cluster of regulatory genes including farA, belongs to the family of pseudoreceptor regulator genes, and that the expression of farR2 is controlled by the IM-2/FarA regulatory system. Disruption of farR2 resulted in delayed production of indigoidine and in transcriptional derepression of the clustered far regulatory genes. Moreover, FarR2 bound to the FarA-binding sequences in the promoter regions of the regulatory genes that were downregulated by FarR2.